Equivalent Circuit Model of Grid-Forming Converters With Circular Current Limiter for Transient Stability Analysis - Fan, Bo; Wang, Xiongfei (IEEE transactions on power systems, 2022)
This letter develops an equivalent circuit model of a grid-forming (GFM) converter with a circular current limiter and analyzes its transient stability. It is revealed that the inner control loop can be simplified as a voltage source behind an equivalent resistor. Based on the developed model, theoretical analysis and experimental tests demonstrate that the transient stability of a P-f droop-controlled GFM converter with the circular current limiter can be assured whenever there exist stable equilibrium points.